Digital Governance Act as an Instrument for Strengthening the European Union's Digital Sovereignty - Sakowska-Baryła, Marlena; Piskorz-Ryń, Agnieszka (Review of European and Comparative Law, 2025)
The Data Governance Act (DGA) aims to support the development of European data spaces in key sectors of the economy, reduce dependence on non-EU suppliers, and strengthen the data-driven economy. In this way, it will strengthen the EU’s digital sovereignty. Achieving these objectives depends on consistent implementation of legislation, the elimination of interpretation gaps, and ensuring a balance between the free flow of data and the protection of public and private interests.